Challenges Encountered in Teaching Four Basic Operations in Mathematics and Academic Performance among Pupils - Abregana, Estella S.; Sabacajan, Bazil T.; Morados, Alexander N.; Nahial, Wenie L. (Future Science / FSH-PH Publications, 2025)
Mathematics is a learning discipline disliked by most of the learners in schools. This became more complicated when the learners transi-tioned from face-to-face to modular learning modality during the pandemic, and just recently from modular back to face-to-face learn-ing modality. This study aimed to determine the extent of the chal-lenges encountered by the respondents in teaching mathematics and the academic performance among the pupils. Using complete enu-meration, all Grades 4 to 6 mathematics teachers in Mambajao Dis-trict were used as respondents of the study. Quantitative descriptive research design was employed supplemented with survey question-naire as the main data gathering tool. Appropriate statistical tools were used to analyse the collected data. Results showed that majority of the respondents were females, middle-aged, with at least 11 years of teaching experience, and with units in master’s degree course pro-gram. The respondents had always experienced challenges in teach-ing mathematics to the learners, while the learners had a satisfactory academic performance. There was no relationship between the ex-tent of the challenges encountered by the respondents and the aca-demic performance of the learners. Finally, the study found no signifi-cant differences on the extent of the challenges encountered among the respondents when grouped in terms of age, sex, number of years of teaching, and highest educational attainment. The researcher rec-ommended that future researchers may replicate this work with ad-ditional interesting variables.